2013
DOI: 10.5005/jp-journals-10032-1012
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Ethnicity and Menopausal Symptoms in Nepal

Abstract: A cross-sectional study was conducted among women of different ethnic groups aged 40 to 60 years and health workers in different parts of Nepal using focus group discussions (FGDs), key informant interviews (KIIs) and clinical examinations to determine the symptoms and complains related to menopause. The mean age at menarche was 15 years and the mean age of menopause was 47. The highest menarche and menopause (50 years) was found to be among the Gurung women. Mean age of menopause was found to be higher among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The mean age of menopause according to the study was found to be 48.35 years with range from 31-52 years. A study done in four districts in Nepal (Kathmandu, Kaski, Makwanpur and Chitwan) have shown a mean age of menopause of 47 years, 11 whereas the study done in Rupandehi District found the mean age to be 46.81 years. 12 A study done within Kathmandu Valley at Nepal Medical College found the mean age of menopause to be 49.9 years with range of 41.5 and 58.3 years.…”
Section: Discussionmentioning
confidence: 91%
“…The mean age of menopause according to the study was found to be 48.35 years with range from 31-52 years. A study done in four districts in Nepal (Kathmandu, Kaski, Makwanpur and Chitwan) have shown a mean age of menopause of 47 years, 11 whereas the study done in Rupandehi District found the mean age to be 46.81 years. 12 A study done within Kathmandu Valley at Nepal Medical College found the mean age of menopause to be 49.9 years with range of 41.5 and 58.3 years.…”
Section: Discussionmentioning
confidence: 91%
“…In a study from four districts of Nepal, mean age of menopause was found to be 47 years 8 . Similarly in another study done in Rupandehi District, the mean age of menopause was 46.81 years 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The menopause and perimenopausal age in developing countries have been reported to be earlier as compared to the developed countries 4 . The average age of menopause in western women is 52-53 years whereas it is 47-49 years in Asian women [7][8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Health Renaissance 2014;12 (2): [87][88][89][90][91] Again this difference can be first attributed to the fact that the study was done in the hospital setting where patient were seen by female doctors only. 10 With regards to the vasomotor symptoms there is much variation.…”
Section: Paudel Et Al Gynaecological and Other Health Problems In Posmentioning
confidence: 99%
“…In Nepal, mean age was 47 years in one study. 2 Although a universal phenomenon, it is a transitional period for women and can be perceived as unpleasant. 3 This natural phenomenon often results in various psychological, somatic and urinary symptoms which impair the overall quality of life of women.…”
Section: Introductionmentioning
confidence: 99%